Tibia and rearfoot motion and ground reaction forces in subjects with patellofemoral pain syndrome during walking - Levinger, Pazit; Gilleard, Wendy (Gait & posture, 2007)
Abnormal subtalar joint function and the consequent rotation of the tibia during walking are thought to contribute to patellofemoral pain syndrome (PFPS). The purpose of this study was to measure rearfoot and tibia motion, and the ground reaction force (GRF) during the stance phase of walking in subjects with PFPS and compare them to healthy subjects. A four camera motion analysis system with a single force plate was used to investigate rearfoot motion relative to the tibia in three planes, the tibial transverse plane rotation and the GRF during the stance phase of walking in 13 female subjects diagnosed with PFPS and 14 healthy females. Analysis showed significantly delayed peak rearfoot eversion ( p = 0.02), and earlier occurrence of peak dorsiflexion ( p = 0.02) for the PFPS group. Furthermore, significantly lower peak medial GRF ( p = 0.03), minimum vertical GRF trough ( p = 0.02) and the second vertical GRF peak ( p = 0.01) were found in the PFPS group. Tibial transverse rotation was not shown to be different in PFPS subjects. However, there was prolonged rearfoot eversion during the stance phase of walking. The earlier appearance of rearfoot dorsiflexion as well as the lower GRFs indicate altered propulsive function of the foot during supination.